Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1017/s1366728918001189
|View full text |Cite
|
Sign up to set email alerts
|

How does childhood bilingualism and bi-dialectalism affect the interpretation and processing of pragmatic meanings?

Abstract: Recent research has reported superior socio-communicative skills in bilingual children. We examined the hypothesis of a bilingual pragmatic advantage by testing bilingual, bi-dialectal and monolingual children on the comprehension and processing of various pragmatic meanings: relevance, scalar, contrastive, manner implicatures, novel metaphors and irony. Pragmatic responses were slower than literal responses to control items. Furthermore, children were least accurate with metaphors and irony. Metaphors and iro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
47
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(52 citation statements)
references
References 86 publications
(123 reference statements)
5
47
0
Order By: Relevance
“…Finally, in Antoniou et al. (2020), the pragmatics test included two items on irony. The researchers reported that ironic items were among the most demanding to interpret for all children.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Finally, in Antoniou et al. (2020), the pragmatics test included two items on irony. The researchers reported that ironic items were among the most demanding to interpret for all children.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Bilingual children's precocious pragmatic development is possibly due to their enhanced executive control skills, or maybe bilingual children develop "heightened pragmatic skills as a compensation of their weaker knowledge of core language" [57]. However, Siegal et al's results, which suggest that bilinguals make more pragmatic interpretations than monolinguals as a function of their enhanced executive functioning control, does not seem to be in line with the results reported by Antoniou and Katsos [36]. Similar to Siegal et al [56], Antoniou and Katsos used a large battery of pragmatic tests that probe into the knowledge of different types of conversational implicature.…”
Section: Scalar Implicatures Among Bilingualsmentioning
confidence: 79%
“…Their study compared the performance of three groups of participants whose years of age range between 6 and 9: (i) monolinguals, (ii) bilectals, and (iii) and multilinguals. Antoniou and Katsos [36] found no statistical difference between bilingual, bilectal, and multilingual children's understanding skills. Multingual and bilectal children exhibited monolingual-like understanding of implicatures; and therefore, there was no multilingual-exclusive pragmatic advantage revealed, consistent with a recent study exploring the pragmatic abilities of Slovenian monolingual and Slovenian-Italian bilingual 10-year-olds [50].…”
Section: Scalar Implicatures Among Bilingualsmentioning
confidence: 90%
See 2 more Smart Citations